Gentlemen’s residences in 1850s Christchurch: an examination of the home of Joseph Brittan and John Cracroft Wilson - Watson, Katharine; Hill, Ian (Architectural History Aotearoa, 2012)
The Canterbury earthquakes have seen the demolitions of many buildings in Christchurch, including some of the city’s earliest building stock. Linwood House was built for John Britten at around the same time as John Cracroft Wilson built Cracroft House. Although both men would have been members of the elite in the new settlement, the first houses they built are quite different. The houses were recorded by archaeologists prior to and during demolition, using the techniques of buildings archaeology. This paper discusses the results of those investigations and considers the similarities and differences between the two houses in terms of both style and construction techniques.